Pertimbangan Hakim dalam Menjatuhkan Putusan Tindak Pidana Narkotika yang Dilakukan Pengedar pada Putusan No: 2071/Pid.Sus/2016/Pn-Mdn - Sirait, Erick Wellington; Rafiqi, Rafiqi (Jurnal Ilmiah Penegakan Hukum, 2018)
Judge's Consideration in Making Narcotics Criminal Decisions Conducted Distributors on Decision No: 2071/Pid.Sus/2016/Pn-Mdn Narcotics circulation and abuse cases in Indonesia are at a very alarming level. This illegal drug easily makes victims in the community, even law enforcement officials involved as dealers and users of drugs. The problem that will be discussed is the judge's consideration of the Narcotics crime in the Decision No. case. 2071 / Pid.Sus / 2016 / PN.Mdn which was decided by the Judge was in accordance with the theory of justice. To discuss this problem, research was carried out using library research methods, namely by conducting research on various written reading sources, and Field Research methods, namely by taking Decision No: 2071 / Pid.Sus / 2016 / PN .Mdn is the case of Narcotics Crime which is related to the title of this Thesis. The results showed that the judges' consideration in dropping and deciding cases of narcotics crimes in the decision No: 2071 / Pid.Sus / 2016 / PN-Mdn was the fulfillment of the elements in article 114 paragraph 2 in conjunction with article 132 paragraph 1 of RI Law No. 35 of 2009 concerning Narcotics as regulated and threatened by crimes according to Article 114 paragraph 1 of RI Law No. 35 of 2009 concerning Narcotics